New ICT Solutions in Public Administration - Aleksandra KUZIOR; Bartosz SOBOTKA (Communications of International Proceedings, 2021)
The article focuses on presenting ICT tools dedicated to public administration. In the era of widespread digitisation, public institutions face the need to implement modern IT systems supporting the work of the office.  The article describes a tool created by a Polish softwear house O4B Friendly declarations. It is a service facilitating the submission of tax returns and municipal waste management fees. The solution has been designed so that taxpayers can easily and quickly fill out a declaration or information on local taxes and send it directly to the appropriate municipality or city office. The innovation of such an approach to the subject of local taxes has been achieved through the introduction of a number of functionalities, including: automatic enrolment of tax rates or automatic selection of attachments.  In addition, the article presents the results of a survey on the willingness to implement e-solutions on a sample of 70 municipalities in Poland through in-depth interviews - IDI and CATI conducted with representatives of local governments (directors/managers of tax departments, IT departments, offices), which, on the one hand, indicate a great need for the implementation of similar solutions and, on the other hand, defined barriers such as: high cost, "mental barrier" and insufficient competence of public institution staff.
Keywords: Friendly declaration; e-administration; ICT tools; local authorities; Integrated Information System